2017
DOI: 10.1523/eneuro.0264-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Emergence of Phenotypes in the Auditory Brainstem Nuclei ofFmr1Knockout Mice

Abstract: Fragile X syndrome (FXS), the most common monogenic cause of autism, is often associated with hypersensitivity to sound. Several studies have shown abnormalities in the auditory brainstem in FXS; however, the emergence of these auditory phenotypes during development has not been described. Here, we investigated the development of phenotypes in FXS model [Fmr1 knockout (KO)] mice in the ventral cochlear nucleus (VCN), medial nucleus of the trapezoid body (MNTB), and lateral superior olive (LSO). We studied feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 79 publications
(97 reference statements)
1
44
1
Order By: Relevance
“…(Borst & Soria van Hoeve, 2012;Forsythe, 1994;Held, 1893;Tolbert & Morest, 1982). It was previously shown that VGLUT2 immunoreactivity in MNTB did not change between ages P6 and P14 in FVB mice (Rotschafer & Cramer, 2017). We found no age-related to our previous findings (Milinkeviciute et al, 2019).…”
Section: Discussionsupporting
confidence: 48%
“…(Borst & Soria van Hoeve, 2012;Forsythe, 1994;Held, 1893;Tolbert & Morest, 1982). It was previously shown that VGLUT2 immunoreactivity in MNTB did not change between ages P6 and P14 in FVB mice (Rotschafer & Cramer, 2017). We found no age-related to our previous findings (Milinkeviciute et al, 2019).…”
Section: Discussionsupporting
confidence: 48%
“…Several recent studies described anatomic alterations in the sound localization pathway of Fmr1 mice, which lead to altered physiologic properties Strumbos et al, 2010;Rotschafer et al, 2015;Garcia-Pino et al, 2017;McCullagh et al, 2017;Rotschafer and Cramer, 2017;Curry et al, 2018;El-Hassar et al, 2019;Lu, 2019). These alterations include differences in synaptic strength and connectivity; differences in postsynaptic ion channels, postsynaptic input resistance, and altered firing properties; alterations in action potential shape; and differences in macroscopic physiologic properties such as ABRs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that Fmr1 −/y mouse strain exhibits sensorial impairments, in addition to behavioral and cognitive alterations similar to those observed in FXS patients (Bakker et al, 1994; Nimchinsky et al, 2001; Yan et al, 2004; Dolen et al, 2007; Spencer et al, 2011; Hebert et al, 2014; Ghilan et al, 2018), concomitantly displaying auditory, olfactory and tactile disorders (Larson et al, 2008; Arnett et al, 2014; Rotschafer and Cramer, 2017). However, to our knowledge, the visual skills of Fmr1 −/y mice have not been investigated using specific visual tests yet.…”
Section: Introductionmentioning
confidence: 92%